Red Rice Bran Ethanol Extract Reduces IL-1β as the Risk of Pancreas Fibrogenesis in Type 2 Diabetic Rat Model - Brian Wasita; Ratih Dewi Yudhani; Dyonisa Nasirochmi Pakha; Diana Nurrohima; Muthmainah Muthmainah; Nanang Wiyono; Shariza Fakurazi (The Indonesian Biomedical Journal, 2025)
BACKGROUND: Oxidative stress and inflammation contribute to pancreatic cell dysfunction that promote insulin resistance in type 2 diabetes (T2D). Red rice bran contains bioactive substances with anti-inflammatory and antioxidant properties which improved insulin resistance in obese mice. However, no studies have explored the potential of ethanol extract of red rice bran (EERRB) to prevent T2D progression, particularly pancreatic fibrosis complications. This study was conducted to investigate the effect of EERRB on inflammation measured with interleukin (IL)-1β and fibrosis of pancreatic tissue in a rat model of T2D. METHODS: Rats were induced with streptozotocin and nicotinamide to induce diabetes, and then separated into five groups. One group received no treatment, while the other four received 9 mg/kg/day acarbose, 165, 330, or 660 mg/kg/day EERRB orally for 21 days. Immunohistochemistry was conducted on pancreas tissues to measure the expression of IL-1β, while pancreatic fibrosis was assessed with Masson’s Trichrome staining.RESULTS: EERRB reduced the expression of pro-inflammatory cytokine, IL-1β, in pancreas tissue in a dose dependent manner. Significantly lower IL-1β expression were found in group receiving 660 mg/kg/day EERRB (10%) compared to diabetic with no treatment group (50%) (p<0.0001). Additionally, the IL-1β expression in the highest dose of EERRB group was comparable to the group receiving acarbose (10%). CONCLUSION: This finding suggests the beneficial effect of EERRB in the hyperglycemic condition that causes oxidative stress through blocking the IL-1β expression, hence alleviating the inflammation in pancreas tissue, and have a tendency in preventing pancreatic fibrosis progression, a process implicated in T2D pathogenesis. KEYWORDS: diabetes, inflammation, pancreatic fibrosis, red rice bran